Improving Students’ Speaking Skills through Artificial Intelligence - Dwi Astuti Febriawati; Muhamad Sofian Hadi (CENDEKIAWAN, 2025)
This study aimed to improve students’ speaking abilities through the use of artificial intelligence in the 2023/2024 school year. The research employed classroom action research involving second-grade students, the researcher, and collaborators. The procedure consisted of planning, action, observation, and reflection. Both qualitative and quantitative data were collected. Qualitative data were obtained through classroom observations, interviews, field notes, photographs, and recordings of the teaching-learning process, while quantitative data were gathered from students’ speaking scores in pre-tests and post-tests, which were analyzed using a t-test. The implementation of artificial intelligence involved the use of English during instruction, engaging media such as pictures, videos, and recordings, feedback on students’ performance, dictionary use, and rewards for active participation. The findings showed that artificial intelligence effectively improved students’ speaking skills, particularly in pronunciation, vocabulary, accuracy, and fluency. Students also became more active, confident, and motivated to speak English and use dictionaries. Overall, the integration of artificial intelligence created a more enjoyable classroom atmosphere and was effective in enhancing students’ speaking abilities.